Development of an icon based programming tool for the ATMEGA microcontroller. - Ng Tong Heng (2023)
This thesis reports on software development project of development an icon based programming tool for ATMEGA microcontroller. The current programming tool for the ATMEGA microcontroller is AVR-C language which is not user-friendly especially for those who does not have the knowledge yet.